Penundaan Pembagian Warisan Bagi Ahli Waris Perantau Minangkabau: Studi Hukum Islam - Fathurrahman, M.; Firmansyah, Heri (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This research aimed to examine the practice of postponing inheritance distribution for Minangkabau migrant inheritors from Islamic law’s perspective and identify the contributing factors. The research employed a mixed-methods approach, combining field research and normative legal analysis. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results showed that postponing inheritance distribution contradicts the principles of Islamic law, which mandates that the division be carried out promptly after the testator’s death using fara’id. This delay is influenced by economic factors, customary practices that grant women a dominant role in inheritance and prioritize the preservation of high-level heirloom treasures, and the distance separating migrant inheritors from their hometowns. Nevertheless, some scholars permit postponement if it is based on considerations of family welfare, while others reject it by referring to the ijbari principle. Therefore, it is recommended that the government, Islamic scholars, Minangkabau indigenous people, and Muslim migrant inheritors enhance their understanding and awareness of Islamic inheritance law and play an active role in preventing and resolving the issue of postponed inheritance distribution, as preventing inheritors from their inheritance rights is unlawful (haram) and a major sin.